Premenstrual syndrome and dysmenorrhea status before and after practicing yoga among selected women of reproductive age group living in Kathmandu valley: A mixed method study - KC, Prakash; Bhandary, Shital (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Premenstrual syndrome and dysmenorrhea are most common gynecological disorders associated with reduced quality of life among women of reproductive age. This study aims to compare the premenstrual syndrome and dysmenorrhea before and after practice of yoga among women of reproductive age living in Kathmandu, Nepal. Surya Namaskar, Surya Kriya and Shambhavi Mahamudra were common yoga types practiced by participants.Method: A retrospective pre-post study with concurrent mixed method design was used. Study respondents were 41 women of reproductive age. Numeric pain rating scale and Premenstrual syndrome scale were used for quantitative data collection. Interview guide was used for the qualitative data collection. Google form was used for quantitative data whereas telephone was used for an in-depth interview. R-4.2.1 software was used for the quantitative data analysis. Qualitative data was analyzed using Braun and Clarke’s 6-steps thematic analysis in RQDA 0.3.8.1 package of R software. Qualitative findings were triangulated with quantitative findings to determine convergent, divergent and expansive findings.Result: All outcome variables pain intensity score (Baseline: 6.46±2.31, Endline: 3.71±2.24, p